Grå reformer och gröna omställningar (Nordic Academic Press, 2026)
The Swedish public administration was profoundly transformed in the years around 1990. The “market” was introduced into policy areas that had previously chiefly been considered the responsibility of society. The book Grå reformer och gröna omställningar (Grey reforms and green transitions) brings together historians and social scientists to explicate the reform projects of these dramatic years. The authors argue that the main purpose of the reforms was often to solve sector-specific problems and that they were “grey” in the sense that they were not primarily ideologically motivated or spearheaded by political actors. The researchers’ case studies of policy sector regulation and deregulation elucidate how reform processes played out in fields such as government housing loans, electricity, environmental governance and the railways. The ambition is to capture the condensed course of events around 1990 and relate it to today’s reawakened interest in a more active state’s capacities in matters like preparedness, energy, climate and housing.